A DSGE Model to evaluate the macroeconomic impacts of taxation - Alves, José (2018)
As recognized, taxation is not only an instrument for government to collect revenues from the economic agents but also an instrument of fiscal policy to influence the agents’ behaviour. In this work, we develop a DSGE model to assess the macroeconomic impact of three tax items (taxes on individual income, on firms’ income and on consumption) on the dynamics of both individual tax items and on the aggregate revenues as well. Moreover, we also intend to evaluate how macroeconomic aggregates behave in a presence of stochastic shocks in taxation.